Clinical management of maggot wounds in Bengal Tigers (Panthera tigris tigris) - Talukder, Anup Kumar; Rahman, Md. Ataur; Park, Sang Hyoun; Chowdhury, Mohammad Nizam Uddin; Haider, Md. Golam; Dey, Tapan Kumar; Rahman, Abu Nasar Md. Aminoor; Das, Ziban Chandra (Journal of Advanced Veterinary and Animal Research, 2017)
Objecitve: Maggot wound is common in domestic and pet animals but report on maggot wound treatment in wildlife species is scanty. The study reported here the surgical and conservative management of maggot wounds including anesthetic protocol and postoperative care in two Bengal tigers (Panthera tigris tigris). Materials and methods: One female and one male tiger were presented with maggot wounds for treatment at the Bangabandhu Sheikh Mujib Safari Park, Gazipur, Bangladesh. Tigers were anesthetized with combined injection of xylazine (dosed at 1.0 mg/kg bwt, IM) and ketamine hydrochloride (dosed at 3.5 mg/kg bwt, IM). Superficial maggots were removed from wounds using sterile tissue forceps. Gauze soaked in oil of turpentine was allowed to remain in each wound pocket for 5 min for the removal of deep-seated maggots. Finally, wounds were dressed with tincture iodine to clean out the dead tissue debris and to induce inflammation for rapid healing. A single subcutaneous injection of ivermectin (dosed at 200 µg/kg bwt, IM) was given in each tiger. In addition, long acting oxytetracycline (dosed at 10 mg/kg bwt, IM) on 48 h interval for six days, chlorpheniramine maleate (dosed at 1 mg/kg bwt, IM) once daily for three days, and ascorbic acid (dosed at 250 mg/tiger, IM) once daily for seven days were administered in both tigers. Results: The tigers were recovered successfully without any complications in two weeks following treatment. Conclusion: Surgical management using oil of turpentine and tincture iodine along with parenteral administration of ivermectin, long acting oxytetracycline and chlorpheniramine maleate are effective for successful management of maggot wounds in Bengal tigers. http://doi.org/10.5455/javar.2017.d187